A difficult history of light. About metaphysical ideas of “light writing” formulated before the birth of photography - Zawojski, Piotr (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
The reflections presented in this article are devoted to Junko Theresa Mikuriya’s book, A History of Light. The Idea of Photography. It is a unique view on the search for pre-photographic origins of photography in the field of philosophical writings ranging from Plato, through the neoplatonic philosopher Jamblich’s enquiry, to the texts by Philotheus of Batos and by an early Renaissance philosopher, Marsilio Ficino. When thinking about metaphysics present in (moving and still) images, one should not forget about the metaphysics of the image itself. The idea of photography – regardless of whether we are witnessing a fundamental change in an ontological transition from an analogue to a digital form of image recording – obliges us to discuss the “history of light”, as this is what Mikuriya does. While locating the discussed concepts in the context of the history and theory of photography, as well as the archaeology of media, the author of this essay engages in a dialogue with Mikuriya and polemically discusses many of her hypotheses. Key concepts such as chalepon, photagogia, triton genos, phôteinographeisthai are analysed in order to indicate inspiring moments in the Mikuriya’s reflections, but also a kind of interpretive abuse in the process of reading and analysing philosophical texts addressing the issues of light.